2022
DOI: 10.7759/cureus.32688
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination: Does It Alter Postoperative Mortality and Morbidity in Hip Fractures?

Abstract: Introduction The primary aim of our study was to evaluate the impact of coronavirus disease 2019 (COVID-19) vaccination on mortality in patients with hip fractures by comparing it to those who are unvaccinated. Our secondary objective was to compare the impact on postoperative morbidity parameters like length of hospital stay and complications. Methods A total of 619 hip fractures were divided into the 'Vaccinated group' consisting of 300 patients who had COVID-19 vaccination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…reported the increased mortality risk in COVID-19 hip fracture patients persisted despite treated surgically [ 33 ]. A few studies also reported on the 90-day mortality rate, which ranged from 14.7% to 67% [ [34] , [35] , [36] ]. Our study demonstrated 90-day mortality rate of 21.4% in COVID-19 hip fracture patients in the Chinese population, which is consistent with overseas studies.…”
Section: Discussionmentioning
confidence: 99%
“…reported the increased mortality risk in COVID-19 hip fracture patients persisted despite treated surgically [ 33 ]. A few studies also reported on the 90-day mortality rate, which ranged from 14.7% to 67% [ [34] , [35] , [36] ]. Our study demonstrated 90-day mortality rate of 21.4% in COVID-19 hip fracture patients in the Chinese population, which is consistent with overseas studies.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccination has been associated with improved outcomes, including decreased mortality, in patients undergoing various surgical procedures, such as cardiovascular, gastrointestinal operations and orthopedic surgeries. [11][12][13] However, there is a paucity of literature evaluating the effect of COVID-19 vaccination on perioperative outcomes after major vascular surgery, specifically. In this retrospective cohort study, we utilized the Society for Vascular Surgery Vascular Quality Initiative (SVS-VQI) database to examine national trends in perioperative mortality after major vascular surgery in the post-vaccination stage of the pandemic.…”
Section: Introductionmentioning
confidence: 99%